Pedagogical practices in teaching duringt he COVID-19 pandemic (Research, Society and Development, 2022)
The pandemic caused by the Coronavirus significantly impacted different social fields in Brazil, including the educational system and its legislation. This situation forced the Brazilian educational system to restructure itself, organizing itself in what became popularly known as Remote Teaching. This achievement was essential to comply with the minimum workload required by law so that students could be promoted to subsequent years, as well as teachers to build their pedagogical practices permeated by educational technologies. Given that, this article was based on identifying the main didactic characteristics and pedagogical practices built by teachers of Basic Education in the Municipality of Itaperuna RJ, during Remote Teaching. The methodology was configured as exploratory, where a semi-structured questionnaire was applied through Google Forms to 54 teachers working in basic education in that municipality. The answers were organized in graphs and tables in order to quantify the results and then promote the research discussion. Therefore, it was possible to identify that: 75% of the teachers chose to use synchronous and asynchronous mixed classes; the synchronous activities corresponded to more than 80% of the works developed; the main technology used was Google Classroom to support remote assistance; more than 90% of teachers pointed to the use of Whatsapp as the main fermentation, 72.4% of teachers reported that schools played a fundamental role in the preparation of classes during remote teaching, however, they still lack greater offers of improvement and/or training courses about technical support for the use of TDICs.